Japan’s Under-Researched Visible Minorities: Applying Critical Race Theory to Racialization Dynamics in a Non-White Society - Debito Arudou (Washington University Global Studies Law Review, 2015)
Critical Race Theory (CRT), an analytical framework grounded in American legal academia, uncovers power relationships between a racialized enfranchised majority and a disenfranchised minority. Although applied primarily to countries and societies with Caucasian majorities to analyze White Privilege this Article applies CRT to Japan, a non-White majority society. After discussing how scholarship on Japan has hitherto ignored a fundamental factor within racialization studies—the effects of skin color on the concept of “Japaneseness”—this Article examines an example of published research on the Post-WWII “konketsuji problem.” This research finds blind spots in the analysis, and re-examines it through CRT to uncover more nuanced power dynamics. This exercise attempts to illustrate the universality of nation-state racialization processes, and advocates the expansion of Whiteness Studies beyond Caucasian-majority societies into worldwide Colorism dynamics in general.
Keywords: race; discrimination; colorism; critical race theory